Supplementation of zinc-chelating peptides from Holothuria scabra improve zinc status in the offspring of zinc-deficient rats - Syahputra, Gita; Louisa, Melva; Gustini, Nunik; Kusumawati, Dwi Endah; Rosyidah, A’liyatur; Putra, Masteria Yunovilsa; Sukria, Heri Ahmad; Wuyung, Puspita Eka; Fadilah, Fadilah; Lee, Hee Jae (Frontiers in Nutrition, 2026)
IntroductionZinc deficiency in children remains a significant health risk, impairing their physical and cognitive maturation. Supplementation with peptide-bound zinc is thought to offer better bioavailability than inorganic zinc salts. Holothuria scabra, commonly referred to as a sea cucumber, contains peptides that may chelate zinc, potentially improving its absorption. The present study aimed to evaluate the efficacy of zinc-chelating peptides from Holothuria scabra (ZCP) supplementation in rat offspring born to zinc-deficient parental rats.MethodsPregnant Sprague Dawley rats were fed either a standard zinc diet (40 mg of zinc per kg of feed) or a zinc-deficient diet (4 mg of zinc per kg of feed). Twelve rat offspring born on the standard zinc diet were randomly assigned to receive either vehicle only or ZCP 40 mg/kg BW. Twenty-four offspring born from zinc-deficient maternal rats were divided into groups that received vehicle only, ZCP 4 mg/kg BW, ZCP 40 mg/kg BW, or ZnSO4 40 mg/kg BW for 3 weeks. At the end of the treatment, serum and intestinal samples were collected and analysed for zinc and metallothionein concentrations, as well as for ZIP2 and ZIP4 mRNA expressions.ResultsZCP supplementation significantly increased serum and duodenal zinc levels, metallothionein concentration, and mRNA expressions of ZIP2/ZIP4 in zinc-deficient rat offspring compared to untreated zinc-deficient ones. Supplementation with ZCP at 4 mg/kg BW showed superior or equivalent improvements compared with ZnSO4 in most parameters.ConclusionZinc chelating peptides from Holothuria scabra improved zinc plasma and duodenal concentrations by enhancing the expression of zinc transporters in zinc-deficient rat offspring. ZCP is a promising alternative to conventional inorganic zinc supplements.